AKIBAT HUKUM PERJANJIAN KREDIT YANG OBYEK JAMINANNYA BUKAN ATAS NAMA DEBITUR - Mahendra, Bagus Priyo (Magister Kenotariatan Universitas Diponegoro, 2018)
AbstractÂ In order to ensure that the debtor performs its obligations, usually in the credit agreement is bound by a guarantee of mortgages or fiducia guarantees to avoid non-fulfillment of the debtor's liability when wanprestasi. The principle of prudence and the maximum crediting limit are important. In practice, the violation occurs as happened to PT BPR